Miopía magna y astigmatismo en paciente femenino de 11 años de edad. - Valero Suarez, Dayanara María (2021)
Myopia is a refractive defect that causes images to focus in front of the retina and not on it, making it difficult to see clearly at far distances. When the visual error exceeds 6-8 diopters we speak of high myopia, (also known as degenerative or pathological myopia) that affects about 2% of the population and increases the risk of developing potentially severe eye diseases. High myopia can occur along with other refractive problems, such as astigmatism. There are no methods to prevent this pathology, so it is important that people at risk undergo periodic check-ups that include an optical examination and a complete ophthalmological examination. For this reason, our objective as an optometrist has the duty to provide primary care to our patients in order to safeguard the care of one of their vital organs. An 11-year-old female patient attends the consultation due to the difficulty in night vision, with correction in use. The patient would have performed her last checkup 10 months ago. Her mother told us that at first she only suffered from high myopia, but when carrying out the corresponding tests she was detected a small astigmatism.